Pathogenesis of experimental tuberculosis in guinea pigs - Sivagiri Palanisamy, Gopinath, author; Basaraba, Randall J., advisor; Orme, Ian, advisor; Mason, Gary L., committee member; Bowen, Richard Arnold, committee member (Colorado State University. Libraries, 2010)
Tuberculosis is an important infectious disease of humans that can be modeled in a number of small laboratory animal species. In humans and guinea pigs, infection with the causative agent Mycobacterium tuberculosis, incites a chronic inflammatory response in the lung (pulmonary) and other (extra-pulmonary) tissues and organs of the body. Granulomatous inflammation can become organized into a distinct inflammatory mass referred to as a granuloma. Granuloma formation is thought to represent a favorable host response that functions to contain the infection, thus preventing spread within or between susceptible hosts. If infected cells within the granuloma die, intracellular bacteria are released and become entrapped in an extra-cellular microenvironment where they persist for long periods of time protected from drug therapy and the host immune response. The mechanism responsible for granuloma cell death (necrosis) is unknown but is important to understand as it represents a unique microenvironment for drug-tolerant bacilli to persist. One potential mediator of granuloma necrosis is the generation of cell and tissue damaging oxygen free radicals, also known as reactive oxygen species (ROS), a hypothesis tested in these studies. We used the guinea pig model of human tuberculosis to test what influence bacterial strain had on the development of pulmonary and extra-pulmonary granuloma necrosis. Our studies showed that the virulence of clinical isolates of M. tuberculosis was reflected in more severe and widely disseminated disease in experimentally infected guinea pigs and was a better predictor of virulence than the bacterial burden determined by culture. These data provide supporting evidence that the extent of lesion necrosis correlated with the severity of disease and is an important determinant in the clinical outcome of tuberculosis. We concluded that both host and pathogen factors contribute to the pathogenesis of lesion necrosis during M. tuberculosis infection. To determine the host factors that contribute to the pathogenesis of lesion necrosis, we focused on the role ROS generation has in the pathogenesis of lesion necrosis in experimental tuberculosis and explored whether this adverse response could be controlled therapeutically or through vaccination of guinea pigs with M. bovis BCG prior to virulent challenge. We found that depletion of host antioxidant defenses was a major determinant in the imbalance between the generation of ROS and host antioxidant capacity in this tuberculosis model. Moreover, we attributed the decreased expression of key antioxidant proteins to a defect in the function of a critical antioxidant transcription factor, nuclear factor-erythroid 2-related factor 2 (Nrf2). We were able to partially restore Nrf2-mediated antioxidant defenses therapeutically in M. tuberculosis infected guinea pigs with the antioxidant drug N-acetylcysteine. We also established that low density lipoproteins were among the host macromolecules that are oxidized during the chronic inflammatory response typical of tuberculosis. Oxidized low density lipoproteins (OxLDL), known to be rich in cholesterol, accumulated in macrophages during infection and elevation of OxLDL levels was accompanied by increased expression of the OxLDL scavenger receptors CD36 and LOX-1. The significance of these data are that through the use of the guinea pig tuberculosis model, we have uncovered a previously unrecognized mechanism by which the host and pathogen interact to create a unique microenvironment that allows difficult to treat M. tuberculosis to persist. The characterization of these host-pathogen interactions may lead to the development of novel adjunct therapies aimed at preventing the adverse effect of M. tuberculosis infection in humans.
Department Head: Sandra L. Quackenbush.
Keywords: oxidative stress; necrosis; guinea pig; granuloma; foam cells; Mycobacterium tuberculosis -- Animal models; Guinea pigs -- Tuberculosis; Virulence (Microbiology); Tuberculosis -- Pathogenesis; Mycobacterium tuberculosis